CHIEF EDITOR FOREWORD - Лялько, В. І. (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2014)
CHIEF EDITOR FOREWORD